2016
DOI: 10.1002/2015wr018300
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments to explain multiscale hydrological responses to mountain pine beetle tree mortality in a headwater watershed

Abstract: The effects of mountain pine beetle (MPB)‐induced tree mortality on a headwater hydrologic system were investigated using an integrated physical modeling framework with a high‐resolution computational grid. Simulations of MPB‐affected and unaffected conditions, each with identical atmospheric forcing for a normal water year, were compared at multiple scales to evaluate the effects of scale on MPB‐affected hydrologic systems. Individual locations within the larger model were shown to maintain hillslope‐scale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 74 publications
5
70
1
Order By: Relevance
“…As in other studies, we found that at the size of the basin and the land cover variability can obscure the signal of change (Biederman et al, 2015;Penn et al, 2016). When we consider forested regions only, we are able to understand how and why streamflow is projected to change under the disturbed conditions.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…As in other studies, we found that at the size of the basin and the land cover variability can obscure the signal of change (Biederman et al, 2015;Penn et al, 2016). When we consider forested regions only, we are able to understand how and why streamflow is projected to change under the disturbed conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Streamflow decreases were previously reported for the upper CRB at Lee's Ferry using the Variable Infiltration Capacity (VIC) hydrologic model (Liang et al, 1994(Liang et al, , 1996 forced with future climate change scenarios alone and reported decreased future projected streamflow (Christensen and Lettenmaier, 2002). A separate study reported that the CRB streamflow is highly sensitive to precipitation and temperature shifts, with large reductions in streamflow estimated for small increases in precipitation and temperature (Nash and Gleick, 1991) resulting from enhanced rates of evapotranspiration.…”
Section: K E Bennett Et Al: Climate-driven Disturbances In the Sanmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent hydrologic research, however, has shown no identifiable change in water yield in response to infestations (Biederman et al, ). Heightened moisture availability, along with less canopy shading and understory regrowth, serves to increase ground evaporation and partially offset transpiration losses (Penn et al, ), which dampens MPB signal at larger scales (Biederman et al, ; Brown et al, ; Penn et al, ). Other field (Bearup et al, ) and modeling (Bearup et al, ) studies suggest that while overall runoff may remain largely dampened by scaling behavior and compensating factors, groundwater contribution to streamflow significantly increases following outbreak.…”
Section: Introductionmentioning
confidence: 99%